2021
DOI: 10.1089/vbz.2021.0016
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Clinical Phenotypes Associated with Severity in Patients with COVID-19 in Northeast Mexico

Abstract: Objective: The aim of this study is to describe the main clinical phenotypes, laboratory findings, and severity of coronavirus disease 2019 in patients hospitalized at the High Specialty Medical Unit # 71 of the Mexican Social Security Institute. Methods: Prospective observational cohort study with a total of 105 patients hospitalized with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection at the High Specialty Medical Unit # 71 (Torreón, Coahuila, Mexico), from May 15th to August 15th, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Garcia-Alvarado et al in their study obtained similar results which stated that the most clinical severity was moderate (62.7%), followed by severe (21.5%), and critical (15.6%). 15 Long et al observed that the most clinical severity was severe (41.7%), followed by moderate (33.9%) and critical clinical severity (24.3%). 12 A higher proportion of moderate symptoms in this study was also associated with exclusion criteria which excluded the comorbidities of stroke and malignancy, pregnancy, as well as younger age.…”
Section: Resultsmentioning
confidence: 99%
“…Garcia-Alvarado et al in their study obtained similar results which stated that the most clinical severity was moderate (62.7%), followed by severe (21.5%), and critical (15.6%). 15 Long et al observed that the most clinical severity was severe (41.7%), followed by moderate (33.9%) and critical clinical severity (24.3%). 12 A higher proportion of moderate symptoms in this study was also associated with exclusion criteria which excluded the comorbidities of stroke and malignancy, pregnancy, as well as younger age.…”
Section: Resultsmentioning
confidence: 99%